2016
DOI: 10.1099/mic.0.000255
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that COG0325 proteins are involved in PLP homeostasis

Abstract: Pyridoxal 59-phosphate (PLP) is an essential cofactor for nearly 60 Escherichia coli enzymes but is a highly reactive molecule that is toxic in its free form. How PLP levels are regulated and how PLP is delivered to target enzymes are still open questions. The COG0325 protein family belongs to the fold-type III class of PLP enzymes and binds PLP but has no known biochemical activity although it occurs in all kingdoms of life. Various pleiotropic phenotypes of the E. coli COG0325 (yggS) mutant have been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
126
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(142 citation statements)
references
References 79 publications
(78 reference statements)
10
126
6
Order By: Relevance
“…The complementation of yggS − E. coli by COG0325 genes of other species and the phenotypic similarities of this E. coli mutant and of the S. elongatus pipY − mutant are strong indications that the function of COG0325 genes is conserved across phyla. The alleviation by PLP or by vitamin B 6 supplementation of the alterations observed in these mutants , best illustrated by the vitamin B 6 dependence of the epilepsy due to PROSC deficiency , indicates that this conserved function is related to PLP, in line with the fact that COG0325 products are PLP‐containing proteins. Yet, previous work has not favored an enzymatic role of COG0325 proteins.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The complementation of yggS − E. coli by COG0325 genes of other species and the phenotypic similarities of this E. coli mutant and of the S. elongatus pipY − mutant are strong indications that the function of COG0325 genes is conserved across phyla. The alleviation by PLP or by vitamin B 6 supplementation of the alterations observed in these mutants , best illustrated by the vitamin B 6 dependence of the epilepsy due to PROSC deficiency , indicates that this conserved function is related to PLP, in line with the fact that COG0325 products are PLP‐containing proteins. Yet, previous work has not favored an enzymatic role of COG0325 proteins.…”
Section: Discussionmentioning
confidence: 88%
“…A, inset). Similarly to the E. coli and yeast COG0325 gene products, YggS, and YBL036C , PipY was monomeric, judged from its behavior in size exclusion chromatography assays (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymes utilizing PLP as a cofactor are found in all organisms and catalyze diverse reactions mostly associated with amino acid as well as neurotransmitter metabolism among other pathways . Little is known about regulation of PLP‐homeostasis …”
Section: Introductionmentioning
confidence: 99%
“…PLPHP is likely to be a protein with dual localization, in both cytoplasm and mitochondria . It has a PLP‐binding domain, but no enzymatic activity . Darin et al suggested that PLPHP acts as a PLP‐carrier that prevents PLP from reacting with other molecules, supplies it to apo‐enzymes, and protects it from intracellular phosphatases .…”
Section: Introductionmentioning
confidence: 99%